The Oxford Handbook of Evolutionary Psychology and Parenting 2021
DOI: 10.1093/oxfordhb/9780190674687.013.11
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and Culture

Abstract: This chapter examines the role of culture in parenting. Although successful parenting involves the use of many skills, cultural and otherwise, rituals provide a blueprint that parents, generation after generation, can and have used to influence their children to emulate proper social behavior. Rituals are used to teach children not only what the behavioral codes are, but how to interpret and respond appropriately to social cues. These parental tactics, to the extent they remain traditional, also teach children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Sensitive caregivers were open to changing the path of the task according to the child's needs, i.e., playing with water if the child started to do it and letting the child lead the activity. Maybe the reason why previous studies reported a lack of pleasant sharing child-caregiver moments in Ethiopia is that they were looking for Western typical dyadic moments, such as playing with toys together and reading books, leaving out all the other important dyadic activities that characterize these child-caregiver interactions (Ringness and Gander, 1974;Cherie and Berhanie, 2015;Coe and Clark, 2021). For instance, Ringness and Gander (1974) reported the prevalence of unsupervised play in young Ethiopian children, a behavior not present in American families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitive caregivers were open to changing the path of the task according to the child's needs, i.e., playing with water if the child started to do it and letting the child lead the activity. Maybe the reason why previous studies reported a lack of pleasant sharing child-caregiver moments in Ethiopia is that they were looking for Western typical dyadic moments, such as playing with toys together and reading books, leaving out all the other important dyadic activities that characterize these child-caregiver interactions (Ringness and Gander, 1974;Cherie and Berhanie, 2015;Coe and Clark, 2021). For instance, Ringness and Gander (1974) reported the prevalence of unsupervised play in young Ethiopian children, a behavior not present in American families.…”
Section: Discussionmentioning
confidence: 99%
“…Many caregivers involved their children in typical daily activities in Ethiopia, such as preparing traditional coffee, eating, taking care of hair dreads, and accomplishing housekeeping tasks. These daily routines are essential occasions to transmit cultural traditions and habits while sharing playful dyadic caregiver–child moments ( Coe and Clark, 2021 ). Sensitive caregivers were open to changing the path of the task according to the child’s needs, i.e., playing with water if the child started to do it and letting the child lead the activity.…”
Section: Discussionmentioning
confidence: 99%